Stability of Weyl points in magnetic half-metallic Heusler compounds - Chadov, Stanislav; Wu, Shu-Chun; Felser, Claudia; Galanakis, Iosif (Physical Review B, 2017)
We employ ab initio fully relativistic electronic structure calculations to study the stability of the Weyl points in the momentum space within the class of the half-metallic ferromagnetic full Heusler materials, by focusing on Co2TiAl as a well-established prototype compound. Here we show that both the number of the Weyl points together with their k-space coordinates can be controlled by the orientation of the magnetization. This alternative degree of freedom, which is absent in other topological materials (e.g., in Weyl semimetals), introduces functionalities that are specific for the class of half-metallic ferromagnets. Of special interest are crossing points which are preserved irrespective of any arbitrary rotation of the magnetization axis.
CRIS-Team Scopus Importer:2022-04-14